Stabilized Detection Accuracy Maximization Using Adaptive SAR Image Processing in LEO Networks - Kim, Kyeongrok; Lee, Jung Hoon; Jung, Soyi; Kim, Joongheon; Kim, Jae Hyun (IEEE Transactions on Vehicular Technology, 2022)
The use of low Earth orbit (LEO) satellites for world-wide surveillance services is currently actively discussed and developed because the constellation of satellites is one major approach which can provide global seamless network services. Because synthetic aperture radar (SAR), which is used for satellite image acquisition and its related signal processing, is dealing with large volumes of image data, corresponding on-demand adaptive methods for SAR image processing are essentially required for stabilized surveillance services under the consideration of data burst situations. Thus, an adaptive vision algorithm for ship detection which is one of major tasks in SAR image processing researches is proposed based on Lyapunov optimization framework, which maximizes the detection performance while satisfying stability conditions. The high-performance filters are utilized for precisely recognizing the targets whereas they introduce relatively larger delays (i.e., tradeoff exists between performances and delays). Therefore, the proposed Lyapunov optimization-based adaptive filter selection algorithm is designed based on the characteristics. Our data-intensive performance evaluation results prove that the proposed algorithm achieves desired performance improvements.
Keywords: Filtering algorithm; Filtering theory; Lyapunov optimization; Marine vehicles; Optimisations; Radar image processing; Radar polarimetry; Stability analyze; Synthetic aperture radar images; Targets detection; adaptive filtering; Low Earth orbit; Lyapunov optimization; synthetic aperture radar; target detection